Effect of cold storage on total phenolics content, antioxidant activity and vitamin C level of selected potato clones. (12th February 2013) - Külen, Oktay; Stushnoff, Cecil; Holm, David G
Abstract BACKGROUND Twelve Colorado‐grown specialty potato clones were evaluated for total phenolic content, antioxidant activity and ascorbic acid content at harvest and after 2, 4, 6 and 7 months cold storage at 4 °C. Potato clones were categorized as pigmented ('CO97226‐2R/R', 'CO99364‐3R/R', 'CO97215‐2P/P', 'CO97216‐3P/P', 'CO97227‐2P/P', 'CO97222‐1R/R', 'Purple Majesty', 'Mountain Rose' and 'All Blue'), yellow ('Yukon Gold') and white fleshed ('Russet Nugget', 'Russet Burbank'). Folin–Ciocalteu reagent was used to estimate total phenolic content, and 2, 2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) diammonium salt (ABTS+) and 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging assays were used to estimate antioxidant capacity. RESULTS Pigmented potato genotypes had significantly higher total phenolic content and antioxidant activity at all data points than yellow‐ and white‐fleshed cultivars. Vitamin C content was higher in 'Yukon Gold' than in the other clones. The highest level of vitamin C in all clones was at harvest and after 2 months in cold storage. Vitamin C content in all potato clones dropped rapidly with longer intervals of cold storage. Although total phenolic content and antioxidant activity fluctuated during cold storage, after 7 months of cold storage their levels were slightly higher than at harvest. Total phenolic content was better correlated with Trolox equivalent antioxidant capacity (TEAC)/ABTS+ than the TEAC/DPPH radical scavenging assay. CONCLUSION Pigmented potato clones had significantly higher total phenolic content and antioxidant activity, while the yellow‐fleshed potato cultivar 'Yukon Gold' had significantly higher vitamin C content. Vitamin C content decreased in all potato clones during cold storage, while total phenolics increased in pigmented clones. © 2013 Society of Chemical Industry